Mono and tri-nuclear cobalt(III) complexes with sterically constrained phenol based N2O2 ligand: Synthesis, structure and catechol oxidase activity. (1st April 2020) - Ali, Imran; Mandal, Bikramaditya; Saha, Rajat; Ghosh, Rajarshi; Chandra Majee, Mithun; Mondal, Dhrubajyoti; Mitra, Partha; Mandal, Debdas
Graphical abstract: Highlights: Mono and tri- nuclear Co(III) complexes, [Co3 (OMe)4 L2 ]ClO4 (1) and [CoL(acac)] (2 ) have been synthesized. Nuclearity of these complexes depends upon the nature of the metal salt used. The structure of the complexes was characterized by single crystal X-ray crystallography and others spectroscopic techniques. Catechol oxidase activity of the complexes was observed. Abstract: Mono and tri- nuclear Co(III) complexes, [Co3 (OMe)4 L2 ]ClO4 (1) and [CoL(acac)] (2 ) have been synthesized using sterically constrained tetradentate ligand N, N / -dimethyl-N, N / -bis(2-hydroxy-3, 5-dimethylbenzyl)-ethylenediamine (H2 L) with varying reaction condition. All complexes have been characterized by single crystal X-ray diffractometer and various spectroscopic tools. Complex 1 is tri-nuclear methoxo and phenoxo bridged cobalt complex with Co III – Co III – Co III linear core, whereas complex 2 is mononuclear mixed ligand octahedral Co(III) complex. Both complexes show catechol oxidase activity in methanol as monitored by the UV–Vis spectroscopy of the aerial oxidation of 3, 5-DTBC to 3, 5-DTBQ. The kinetic parameters have been determined using Michaelis–Menten approach. The complexes are efficient catalysts with high turnover numbers 3.32 × 10 3 h −1 and 2.19 × 10 3 h −1 for 1 and 2, respectively. Mechanistic investigations of the catalytic behaviour by ESI-MS spectra and estimation of hydrogen peroxide formation indicates that the catalytic reaction occurs through the reduction of Co(III) to Co(II).